Re-description of Trypanosoma corvi Stephens and Christophers,1908 Emend. Baker, 1976 and remarks on the Trypanosomes of the Avian Family Corvidae - N. C. Nandi; Gordon F. Bennett (Memorias do Instituto Oswaldo Cruz, 1994)
The trypomastigote, epimastigote and amastigote stages of Trypanosoma corvi Stephens and Christophers, 1908 emend. Baker, 1976 from the peripheral blood, heart and bone marrow are described herein. Other trypanosomes described from the Corvidae are compared to T. corvi and their status is discussed.